The role of the diabetologist in prevention of diabetic foot syndrome - Ducka, Bernadeta; Strojek, Krzysztof (Przewodnik Lekarza/Guide for GPs, 2007)
This article presents the role of the diabetologist in everyday practice in prevention of diabetic foot syndrome. It points to education as an important factor in prophylaxis of this disorder